The association between treatment adherence to nicotine patches and smoking cessation in pregnancy: a secondary analysis of a randomised controlled trial - Vaz, Luis R.; Aveyard, Paul; Cooper, Sue; Leonardi-Bee, Jo; Coleman, Tim (Oxford University Press, 2016)
Introduction